Lenguaje literal y connotado en la enseñanza de las Ciencias - Lahore Alberto, A. (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 2006)
This article intends to be a reflection on the function of language in science learning, and a possible explanation of the difficulties encountered by students in the use and interpretation of scientific language.